2020
DOI: 10.3389/fonc.2020.550171
|View full text |Cite
|
Sign up to set email alerts
|

Lugol’s Iodine-Enhanced Micro-CT: A Potential 3-D Imaging Method for Detecting Tongue Squamous Cell Carcinoma Specimens in Surgery

Abstract: Background: A positive surgical margin (PSM) following oral cancer resection results in local recurrence and poor prognosis. Mono-block tumor specimens, especially from the tumor base, are difficult to evaluate. This inaccurate sampling ultimately leads to a false pathological diagnosis. Lugol's iodine (I 2-IK)-enhanced micro-CT is an emerging method to image tumor specimens. This study explores the feasibility of I 2-IK-enhanced micro-CT to evaluate the surgical margin for tongue squamous cell carcinoma (TSCC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…This is in accord with the fact that muscles are rich in glycogen. In addition, in our previous study, we also found that I 2 -IK has different affinity for OSCC cells in culture with high and low glycogen ( 25 ). It reminded us that the glycogen content of tumor tissues maybe richer than that in normal tissue in LNs.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…This is in accord with the fact that muscles are rich in glycogen. In addition, in our previous study, we also found that I 2 -IK has different affinity for OSCC cells in culture with high and low glycogen ( 25 ). It reminded us that the glycogen content of tumor tissues maybe richer than that in normal tissue in LNs.…”
Section: Discussionmentioning
confidence: 73%
“…Due to the low price, Lugol’s iodine (I 2 -IK) has already been widely used to assist micro-CT to delineate the internal fine anatomic structure of various soft tissue samples ( 19 23 ). In oncology, I 2 -IK-enhanced micro-CT imaging has also been used to provide the 3D structural information in adamantinomatous craniopharyngioma ( 24 ) and OSCC ( 25 ). However, no study has reported the use of I 2 -IK enhanced micro-CT imaging to accurately locate the metastatic foci.…”
Section: Introductionmentioning
confidence: 99%
“…To achieve this, it is necessary to produce a clear WTI with no staining defects. Xia et al reported that favorable Micro-CT images were obtained by staining tongue squamous cell carcinoma specimens with 3% Lugol's iodine solution for 12 h 20 . The ESD specimens used in this study were collected in routine clinical practice, and we cannot perform any protocol that would affect the conventional pathological diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…µCT has been used as an X-rays based imaging techniques, to characterize blood clot composition, its etiology and its amenability for pharmacological treatment, and a better understanding of thrombus structure and composition. In this study, we stained the blood clot with Lugol's iodine solution which increases and enhance µCT to evaluate blood clot imaging [16].…”
Section: Discussionmentioning
confidence: 99%